ANALISIS FAKTOR YANG BERPENGARUH TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2014-2016 - M Shodiqur Rifqi, 14.05.52.0195; Wardjono, Wardjono (Students Journal of Accounting and Banking, 2018)
This study examines the effect of profitability, leverage, company size, company growth, institutional and managerial ownership of company value on the manufacturing companies listed in a BEI period of 2014-2016. The population in the current study is the listed companies in the Indonesia Stock Exchange from 2014 to 2016. I used a purposive sampling method for selecting the samples, and totally obtained 227 samples. The result of this study shows that profitability has a significant positive effect on company value; leverage has a significant negative effect on company value; company size has a significant positive effect on company value; company growth has an insignificant negative effect on company value; institutional ownership has an insignificant positive effect on value; and managerial ownership has an insignificant negative effect on company value.Keywords: profitability, leverage, company size, company growth, institutional ownership, managerial ownership and company value